PENGARUH PELATIHAN MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN SATPAM PT PERTAMINA HULU SANGA SANGA DI MUARA BADAK - Kolibu, Melisa Marini; Aryani, Farida; Hendra (SEKOLAH TINGGI ILMU EKONOMI TENGGARONG, 2023)
The purpose of this study was to determine the effect of training, motivation and discipline variables partially and simultaneously on the performance of security personnel at PT. Pertamina Hulu Sanga Sanga. The sample in this study were 82 people. The data analysis technique in this study is multiple regression with hypothesis testing using the f test and t test. The research results obtained simultaneously variable training, motivation and discipline have a significant effect on the performance of security personnel at PT. Pertamina Hulu Sanga. The results of this study partially three variables training, motivation and discipline have a significant effect on security guards employees of PT. Pertamina Hulu Sanga Sanga. The most dominant variable is the motivation variable